Corrosion casting of the cardiovascular structure in adult zebrafish for analysis by scanning electron microscopy and X‐ray microtomography. (29th January 2020) - De Spiegelaere, Ward; Caboor, Lisa; Van Impe, Matthias; Boone, Matthieu N.; De Backer, Julie; Segers, Patrick; Sips, Patrick
Abstract: Zebrafish have come to the forefront as a flexible, relevant animal model to study human disease, including cardiovascular disorders. Zebrafish are optically transparent during early developmental stages, enabling unparalleled imaging modalities to examine cardiovascular structure and function in vivo and ex vivo. At later stages, however, the options for systematic cardiovascular phenotyping are more limited. To visualise the complete vascular tree of adult zebrafish, we have optimised a vascular corrosion casting method. We present several improvements to the technique leading to increased reproducibility and accuracy. We designed a customised support system and used a combination of the commercially available Mercox II methyl methacrylate with the Batson's catalyst for optimal vascular corrosion casting of zebrafish. We also highlight different imaging approaches, with a focus on scanning electron microscopy (SEM) and X‐ray microtomography (micro‐CT) to obtain highly detailed, faithful three‐dimensional reconstructed images of the zebrafish cardiovascular structure. This procedure can be of great value to a wide range of research lines related to cardiovascular biology in small specimens.